Evaluating Downtown Urban Heat Island Effect : The Case Of Adama City, Ethiopia - Ayalnesh, Shawul (ASTU, 2023)
The Urban Heat Island Is The Main Problem Of Larger Cities And Metropolitan Areas Across The World. Now A Day???S, Developing Countries Like Ethiopia Are Characterized By High Urbanization. As One Of The Cities Of Ethiopia, Adama Is Also A Rapidly Urbanizing City, Which Resulted In Impervious Surfaces That Caused An Increase In Temperature, Especially In The Inner Part Of The Town. Accordingly, In The Downtown Area Of Adama City, The Magnitude Of The Urban Heat Island Is Increasing Compared To The Nearest Rural Areas, Which Affects The Well-Being And Comfort Of The Inhabitant Mostly In The Winter Season. Thus, The Study Intends To Assess The Causes And Effects Of Urban Heat Islands And Provide Measures To Mitigate The Downtown Urban Heat Island Effect Of Adama City By Analyzing The Land Surface Temperature And Estimating The Spatial-Temporal Changes Within The Years 2013 And 2023. The Study Is Conducted Based On Both Qualitative And Quantitative Approaches Using Different Models And Data, Arch GIS, Satellite Images, And Survey Methods. The Primary Data Was Acquired By Using Questionnaires, Interviewing, And Photography To Identify The Factors And Effects Of Urban Heat Islands In The City. Secondary Data Like Satellite Images Were Also Used. GIS Software Was The Main Computer Packages Used To Analyze Spatial-Tempo Data. The Results Of This Study Indicate That The Magnitude Of The Urban Heat Island In The Downtown Area Of The City Is 5oC To 7.5oC. The Area Of Non-Vegetated And Non-Reflective Surfaces Has 75% (High) Lst Than Those Vegetated Surfaces, Which Is 25%. On The Other Hand, The Result Of Lu/Lc Change Indicates That In The Period Between 2013 And 2023, The Built Area Showed Incremental Changes By +1597ha, While Shrubs And Bare Land Decreased By -194 And (-649) Ha, Respectively. This Confirms That The Maximum Uhi Occurs Because Of The Increasing Built-Up Area. In Addition, Increasing The Usage Of Low Albedo Material For Paving As Well As For Different Construction Of The Structure In The City Has A High Contribution To The Increment Of Uhi In The Study Area. The Finding Also Indicates An Increase In Uhi Affecting The Well-Being Of Urban Dwellers By Causing Discomfort And Affecting The Health Of The Residents, Especially In The Winter Season. Therefore, This Study Recommends Greening Roofs, Planting Vegetation Along The Roadside And Buildings, Improving Pavement Materials, Promoting Cool Roofs And High Albedo Building Materials, Etc., For Mitigating Uhi In Downtown.
Keywords: Albedo, Land Surface Temperature, Normalized Difference, Spatial-Temporal, Urban Heat Island